Peran Tenaga Pendidik Dalam Mengembangkan Pola Belajar Siswa di SMK Tunas Berkarya Batam - Wasiman Wasiman (Universitas Pahlawan Tuanku Tambusai, 2022)
The era of globalization demands the role of teachers to adapt to the challenges that are not easy in teaching and fostering students who are their duties and responsibilities as educators. Tri Dharma of Higher Education as a guide for lecturers in carrying out their duties as educators. Community service, on this occasion carried out at SMK Tunas Muda Berkarya Batu Aji Batam. The purpose of service is to conduct training for Educators in Developing Effective Learning Patterns for students. The method we use is to give presentations and discussions for 1 hour and 30 minutes to educators and students so that we get input on appropriate learning for students and efficient methods in implementing learning to students. The results of the service concluded that the increasing understanding of teachers about effective learning patterns applied to students by combining offline and online learning and hubryd learning learning so that students become many alternative learning options that are not boring.